Analysis of the Current Performance of Meat Processing Industry in Ukraine - A. L. Koliada (Статистика України, 2016)
In the conditions of market economy, characterized by fierce competition and high requirements to end products, a comprehensive analysis of the current performance of the meat-processing industry becomes increasingly important. The effective operation of any industry largely depends on proper analysis of change in its internal and external environment. Analysis of the current performance of meat processing enterprises in Ukraine has essential importance for setting up priority measures for further enhancement of the industry performance and elaboration of comprehensive recommendations which, once implemented, can improve the industry performance.